Efficient Rooting System for Apple “M.9” Rootstock Using Rice Seed Coat and Smocked Rice Seed Coat - Matiullah Akbari; Tsutomu Maejima; Shungo Otagaki; Katsuhiro Shiratake; Shogo Matsumoto (International Journal of Agronomy)
“M.9” rootstock is considered as one of the most useful apple (Malus x domestica Borkh.) rootstocks; it produces dwarfing trees efficiently. As “M.9” rootstock shows a poor, brittle, and shallow roots system, we grafted “M.9” rootstocks onto “Marubakaidou” (M. prunifolia Borkh. var. ringo Asami Mo 84-A). We then propagated them by mound layering to establish a high-density root system. It was found that covering the roots with rice seed coat (RSC), RSC + smoked rice seed coat (SRSC), and vermiculite during mound layering was effective for the initiation of rooting. Utilizing RSC and SRSC seemed especially effective for producing “M.9” roots efficiently.